Ethnic Identity Politics and Voter Behavior: The 2018 West Kalimantan Gubernatorial Election - Rahardian Putra Setia Budi; Ganjar Razuni (The Kalimantan Social Studies Journal, 2025)
This study examines the influence of ethnic identity politics on voter behavior in the 2018 West Kalimantan gubernatorial election, focusing on Dayak and Malay ethnic sentiments and candidate strategies in communicating ethnic and religious identity. The research is grounded in post-Reformasi decentralization that enabled ethnic-based political mobilization, alongside historical marginalization of the Dayak and dominance of the Malay during the New Order period, shaping local political dynamics. The study employs a qualitative case study approach with data collected through in-depth interviews, literature review, and documentation, involving key informants such as gubernatorial candidates, ethnic leaders, and political observers. Data analysis follows reduction, presentation, and verification stages to explore the interaction between candidate strategies, ethnic-religious affiliation, and voter behavior. Results indicate that ethnic-religious sentiment significantly influenced the 2018 election outcomes, with Sutarmidji-Ria Norsan winning through consolidation of Malay-Muslim support in coastal areas, while Dayak-Christian voters remained dominant inland. Candidates integrated development narratives with local identity to build public trust, reinforce ethnic-religious voting patterns, and leverage party coalitions and community networks. The findings provide novel insights for ethnic politics, decentralization, and voter behavior studies, highlighting the complex interplay between ethnicity, religion, and campaign strategy in regional elections.